2023
DOI: 10.3390/w16010159
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physicochemical Parameters by Remote Sensing of Bacalar Lagoon, Yucatán Peninsula, Mexico

José Luis Hernández-Martínez,
Jorge Adrián Perera-Burgos,
Gilberto Acosta-González
et al.

Abstract: Remote sensing is an invaluable research tool for the analysis of marine and terrestrial water bodies. However, it has some technical limitations in waters with oligotrophic conditions or close to them due to the low spectral response of some water parameters to the signal from the sensors to be used. In this work, we use remote sensing to evaluate a set of water quality parameters (dissolved oxygen, total dissolved solids, oxidation–reduction potential, electrical conductivity, salinity, and turbidity) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…All these shallow areas are subjected to desiccation during dry weather conditions. Studies reported higher electrical conductivity values in the eastern and northern parts of BL, close to shallower areas [41]. This makes BL very susceptible to climatic and anthropogenic threats.…”
Section: Human-driven Alterationsmentioning
confidence: 96%
See 1 more Smart Citation
“…All these shallow areas are subjected to desiccation during dry weather conditions. Studies reported higher electrical conductivity values in the eastern and northern parts of BL, close to shallower areas [41]. This makes BL very susceptible to climatic and anthropogenic threats.…”
Section: Human-driven Alterationsmentioning
confidence: 96%
“…The pH values ranged from a minimum of 6.6 [39] to a maximum of 8.3 [40]. The northern area of BL features muddy sediments and turbid waters [41], which contrasts with the sandy bottoms of the southern area and the higher Secchi water transparency [42], with values reported at up to 10 m in depth [10].…”
Section: Introductionmentioning
confidence: 99%